Podmiot moralny we współczesnej ochronie zdrowia – dylematy etyczne i dystres moralny w pracy pielęgniarki - Borkowska, Natalia (Civitas hominibus, 2023)
As a health care professional, a nurse should support not only the principle of nonmaleficen-ce, but also beneficence and respect patient’s autonomy and fair distribution of resources.Due to the inclusion of new technologies in patient care, it is worth analysing the need to adapt the existing ethical principles in nursing in order to provide the best possible care,build a therapeutic relationship with the patient and counteract the occurrence of ethicaldilemmas and moral distress.